1999
DOI: 10.1074/jbc.274.43.30451
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of AOEB166, a Novel Mammalian Antioxidant Enzyme of the Peroxiredoxin Family

Abstract: Using two-dimensional electrophoresis, we have recently identified in human bronchoalveolar lavage fluid a novel protein, termed B166, with a molecular mass of 17 kDa. Here, we report the cloning of human and rat cDNAs encoding B166, which has been renamed AOEB166 for antioxidant enzyme B166. Indeed, the deduced amino acid sequence reveals that AOEB166 represents a new mammalian subfamily of AhpC/TSA peroxiredoxin antioxidant enzymes. Human AOEB166 shares 63% similarity with Escherichia coli AhpC22 alkyl hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
169
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(176 citation statements)
references
References 45 publications
4
169
0
Order By: Relevance
“…This dual localization may have functional significance and be related to the observation that TcGPXI can use both tryparedoxin and glutathione as electron donors. Studies on yeast and mammalian peroxiredoxin Vs have shown that these enzymes are distributed in the peroxisome and cytosol (39,(51)(52)(53)(54) and can also use both thioredoxin and glutathione as an electron donor (39,55). Because peroxisomes lack thioredoxin but do contain glutathione (41), it has been proposed that peroxiredoxin V functions as a thioredoxin-dependent enzyme within the cytosol, whereas within the peroxisome the glutathione-dependent activity predominates.…”
Section: Discussionmentioning
confidence: 99%
“…This dual localization may have functional significance and be related to the observation that TcGPXI can use both tryparedoxin and glutathione as electron donors. Studies on yeast and mammalian peroxiredoxin Vs have shown that these enzymes are distributed in the peroxisome and cytosol (39,(51)(52)(53)(54) and can also use both thioredoxin and glutathione as an electron donor (39,55). Because peroxisomes lack thioredoxin but do contain glutathione (41), it has been proposed that peroxiredoxin V functions as a thioredoxin-dependent enzyme within the cytosol, whereas within the peroxisome the glutathione-dependent activity predominates.…”
Section: Discussionmentioning
confidence: 99%
“…The 52 amino acid residues at the NH 2 -terminus of the longer polypeptide were shown to constitute a mitochondrial presequence that is capable of importing a fusion protein of AOEB166 and green uorescent protein into mitochondria. Indeed, immunoblot analysis revealed that Prx V is localized intracellularly to cytosol, mitochondria, and peroxisomes (23).…”
Section: Atypical 2-cys Prx Subgroup Membersmentioning
confidence: 99%
“…PRDX1 and 2, also referred as natural killer enhancing factors (NKEF-A, NKEF-B), are localized in the cytosol [6,7], whereas the other members of the 2-Cys PRDX subclass are widely distributed with PRDX3 in mitochondria [8], PRDX4 in endoplasmatic reticulum and extracellular space [9] and PRDX5 in cytosol, mitochondria and peroxisomes [10]. In contrast, PRDX6 is restricted to cytosol [11], and the catalytic efficiency of all PRDXs is less than that of catalase or glutathione peroxidases by one or three orders of magnitude [12].…”
Section: Introductionmentioning
confidence: 99%